2020
DOI: 10.1590/1676-0611-bn-2020-0975
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic diversity of Biomphalaria (Planorbidae) in São Paulo state, Brazil

Abstract: Abstract: Morphological and molecular identifications were carried out for Biomphalaria occidentalis, Biomphalaria oligoza, Biomphalaria peregrina, Biomphalaria schrammi, Biomphalaria straminea and Biomphalaria tenagophila collected from 55 sites located along the upper basin of Tietê River in the Southeast Region of Brazil. Morphological analysis considered aspects of the shell, mantle, excretory organs and reproductive system. Molecular data included 122 sequences of Cytochrome C Oxidase I gene (COI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…This result is promising regarding the use of DNA barcoding for taxonomy by the schistosomiasis epidemiology service in Brazil. In addition, due to the resolution observed using the Best Close Match (BCM) and BOLD Identification Criteria analyses, DNA barcoding methodology has a great potential to provide greater objectivity for mollusk identification, and can be used for the verification of identification performed by other methods ( Ohlweiler et al., 2020 ). For species of the B. tenagophila complex, despite the proximity between the taxa, the DNA sequences were correctly identified by DNA barcoding methodology, with the analyses performed by BOLD Identification Criteria and BCM .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is promising regarding the use of DNA barcoding for taxonomy by the schistosomiasis epidemiology service in Brazil. In addition, due to the resolution observed using the Best Close Match (BCM) and BOLD Identification Criteria analyses, DNA barcoding methodology has a great potential to provide greater objectivity for mollusk identification, and can be used for the verification of identification performed by other methods ( Ohlweiler et al., 2020 ). For species of the B. tenagophila complex, despite the proximity between the taxa, the DNA sequences were correctly identified by DNA barcoding methodology, with the analyses performed by BOLD Identification Criteria and BCM .…”
Section: Discussionmentioning
confidence: 99%
“…For species of the B. tenagophila complex, despite the proximity between the taxa, the DNA sequences were correctly identified by DNA barcoding methodology, with the analyses performed by BOLD Identification Criteria and BCM . Other authors also successfully separated the species of this complex, using DNA barcoding and phylogenetics, with high support values associated with each of the clades, and concluded that, for this species complex, molecular data may be more informative for species discrimination than morphology ( Ohlweiler et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Os gastrópodes pertencentes a Família Planorbidae são caracóis pulmonados encontrados em ambientes de água doce (Strong et al, 2008), frequentemente registrados em locais com condições de hipóxia, juntamente com Chiromonidae e Oligocheta (Colpo et al, 2009). Além disso, os planorbídeos do gênero Biomphalaria Preston, 1910 são hospedeiros do Schistosoma mansoni Sambon, 1907, agente etiológico da esquistossomose (Ohlweiler et al, 2021). et al, 2007).…”
Section: Discussionunclassified
“…Both susceptible and refractory species may coexist in the same municipality. In São Paulo, in the Southeast Region of Brazil, B. occidentalis, B. oligoza, B. peregrina, B. schrammi, B. straminea and B. tenagophila are present in water bodies of the upper basin of the Tietê River ( 14 ).…”
Section: Geographic Distribution Of Susceptible Species Of mentioning
confidence: 99%